2020
DOI: 10.1109/access.2020.2981163
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamically Phase Tunable Metasurface for a Broad Bandwidth Ultra-Low Radar Cross Section

Abstract: An electrically tunable metasurface is designed for radar cross-section (RCS) reduction application in this paper. It consists of 24 × 24 cells individually loaded with variable capacitors so that their phase profiles can be independently controlled by the bias voltage. Therefore, based on the diffusive scattering principle and reflect-array theory, we arrange the adaptive phase differences between adjacent basic elements and reconfigure the appropriate phase distribution determined by a genetic algorithm (GA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Then, a unit cell configuration exhibiting stable reflection phase over 6. [8][9][10][11][12][13][14][15][16].4GHz is presented. According to Fraunhofer criterion on diffuse scattering, six optimized unit cells with different physical sizes and equal phase gradient are determined to construct the metasurface with random phase distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a unit cell configuration exhibiting stable reflection phase over 6. [8][9][10][11][12][13][14][15][16].4GHz is presented. According to Fraunhofer criterion on diffuse scattering, six optimized unit cells with different physical sizes and equal phase gradient are determined to construct the metasurface with random phase distribution.…”
Section: Discussionmentioning
confidence: 99%
“…From then on, more researchers focus on anomalous electromagnetic phenomena brought by metasurface and it is applied promptly in various fields, including but not limited to wave-front control technology [7] [8], polarization convertor, propagating waves(PW) to surface waves(SW) convertor [9] [10], ultrathin flat lenses [11], holographic technology, vortex-beam generators. It is also used to reduce monostatic radar cross section (RCS) [12] [13] [14][15] [16]. For example, it is demonstrated that metasurfaces can be used to realize specific electromagnetic characters such as reflection in specific direction without altering its physical shape, by utilizing achromatic phase shift stemming from spin-orbit interaction in ultrathin space-variant and spectrally engineered metasurfaces [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tunable and reconfigurable metasurfaces are more desirable for rapid developments in multifunctional and multistandard communication systems. Tunable and reconfigurable metasurfaces were achieved by various methods, such as micro-electromechanical systems (MEMS), varactor diode, liquid crystal (LC), etc [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Ferrite is an approach to realize tunability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although MEMS-based metasurfaces exist the advantage of high tuning, they suffer from expensive costs and complicated fabrication processes. Varactor diodes and p-i-n diodes have the characteristics of high tuning or switching speed and large tuning range, which is very suitable for the design of tunable metasurfaces [18][19][20][21][22][23]. For example, four varactor diodes are used in the metasurface unit cell, whose reflection band can be tuned from 1.23 to 2.24 GHz [19].…”
Section: Introductionmentioning
confidence: 99%
“…By integrating tunable components into the meta-atom, the response of the metasurface to incident light can be dynamically modified. Reconfigurability in metasurfaces is typically achieved by optical, thermal, and electrical mechanisms, mechanical stretching, chemical reactions, , and so on. Taking advantage of the digital description possibilities offered by a real-time addressable ultra-thin metasurface, reprogrammable image holography can be achieved with high imaging precision.…”
Section: Introductionmentioning
confidence: 99%